Universality of oscillation theory laws. types and role of mathematical models - Polina S. Landa (Discrete Dynamics in Nature and Society)
The universality of oscillation theory laws is discussed. It is suggested that all models of concrete systems be separated into four categories: models – “portraits” of investigated systems, models of the type of “black box”, aggregating models, and models of certain phenomena which can occur in real systems. As an example of the model of the fourth type, the equation of oscillations of a pendulum with a randomly vibrating suspension axis is considered for the purpose of clarifying the mechanism of the transition to turbulence.